Mental Health Condition of Children Infected with HIV/AIDS - Sureshgouda S Patil; Bharathi M (RGUHS Journal of Nursing Sciences)
Children are at a high risk for many of the medical conditions as their immune system in not completely matured. Children exposed to life-threatening illnesses like HIVAIDS may face a range of potential psychological changes. Psychosocial issues are common among families with any of the family member suffering from HIVAIDS. This paper provides a thorough analysis of the psychological and psychosocial challenges faced by children living with HIVAIDS along with possible suggestions to deal with these issues.